2012
DOI: 10.1063/1.4773361
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon micro- and nanoparticles for printed humidity sensors

Abstract: Accurate measurements of water vapor transmission through high-performance barrier layers Rev. Sci. Instrum. 83, 075118 (2012) Quantitative calcium resistivity based method for accurate and scalable water vapor transmission rate measurement Rev. Sci. Instrum. 82, 085101 (2011) Humidity response properties of a potentiometric sensor using LaF3 thin film as the solid electrolyte Rev. Sci. Instrum. 82, 083901 (2011) New Products Rev. Sci. Instrum. 82, 029501 (2011) Biologically inspired humidity sensor based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…In the second application, PSi nanoparticles have been utilized for the potential cheap mass production of sensor systems. Jalkanen et al produced undecylenic acid treated THCPSi micro‐ and nanoparticle ink, which was used to drop cast fully functional humidity sensors on a glass substrate on the top of inkjet‐printed silver electrodes . Interestingly, a narrow distribution of nanoparticles was found to provide the best adhesion between the particles.…”
Section: Recent Progress In Applications Of Thermally Carbonized Poromentioning
confidence: 99%
“…In the second application, PSi nanoparticles have been utilized for the potential cheap mass production of sensor systems. Jalkanen et al produced undecylenic acid treated THCPSi micro‐ and nanoparticle ink, which was used to drop cast fully functional humidity sensors on a glass substrate on the top of inkjet‐printed silver electrodes . Interestingly, a narrow distribution of nanoparticles was found to provide the best adhesion between the particles.…”
Section: Recent Progress In Applications Of Thermally Carbonized Poromentioning
confidence: 99%
“…Jalkanen et al showed that thermal hydrocarbonization (THC) of PSi also shows a strong decrease in hysteresis. The implementation of this approach allows the development of PSi‐based humidity sensors with negligible hysteresis (Figure ).…”
Section: Approaches To Optimization Of Psi‐based Gas and Vapor Sensorsmentioning
confidence: 99%
“…To impart hydrophilicity to the surface of the film, THCPSi films were treated with undecylenic acid by immersing the films in a solution of undecylenic acid for 12 h at 110 °C. Jalkanen et al believe that this functionalization of the surface minimizes the effect of capillary condensation and increases the role of surface effects in the gas‐detection phenomenon. Bjorkqvist et al showed that the continuous heating of PSi‐based sensors also reduced hysteresis drastically.…”
Section: Approaches To Optimization Of Psi‐based Gas and Vapor Sensorsmentioning
confidence: 99%
“…Both coating and printing processes are of major industrial interest, being frequently encountered in the production of paper products, polymer sheets and a wide range of printed electronics. It is the latter which has attracted increasing attention in recent years, as printing of electronic circuitry and wide area coating, for example, lighting or photovoltaic applications (Krebs, 2009) places new requirements on coating and printing process technologies [ (Michels et al, 2014), (Pudas et al, 2005), (Mäkelä et al, 2007), (Jin et al, 2010), (Jalkanen et al, 2012), (Kumar, 2015)]. …”
Section: Introductionmentioning
confidence: 99%